Anna Julia Cooper's Black Feminist Love‐Politics. (19th August 2016) - May, Vivian M.
Abstract : To flesh out love's potential for transformative imaginaries and politics, it is important to explore earlier examples of Black feminist theorizing on love. In this spirit, I examine Anna Julia Cooper (1858–1964), an early Black feminist educator, intellectual, and activist whose work is generally overlooked in feminist and anti‐racist thinking on love, affect, and social change. Contesting narrow readings of Cooper, I first explore how critics might engage in more "loving" approaches to reading her work. I then delineate some of her contributions to a Black feminist love‐politics. In unmasking dominance enacted in love's name, Cooper analyzes romantic love, marriage, and gendered care‐work in the domestic sphere. Using an intersectional lens, she contests gendered‐raced hierarchies and links normative masculinity and femininity with white supremacy, xenophobia, and imperial rule. Cooper also extolls the possibilities of love rooted in nonhierarchical, intersubjective cooperation: such loving has the potential to transform interpersonal relations and foster broad collaborative action to eradicate inequality, locally and globally. Structural subjection, internalized oppression, and colonized imaginations have no part in Cooper's reciprocal, political love‐force. Unfortunately, her ideas about transforming gender relations, contesting racism, challenging imperialism, seeking decolonized selves, and pursuing solidarity as a loving political orientation remain relatively unknown.